The International handbook on social innovation : collective action, social learning and transdisciplinary research - Moulaert, Frank (Edward Elgar Publishing MassachusettsUS, 2013)
Refers broadly to innovation in meeting social needs of, or delivering social benefits to communities, viz., the cration of new products, services, organisational structures or activities that are better or more effective than traditional, public sector, philanthropic or market-reliant approaches in responding to social exclusion. Presents a coherent methodological perspective on social innovation, both conceptually and practically - to multi-scalar structural, political and cultural forces which produce social exclusion but also hold the potential for social change and socially innovative initiatives.